2020
DOI: 10.1007/s00394-020-02344-8
|View full text |Cite
|
Sign up to set email alerts
|

Estimated dietary pesticide exposure from plant-based foods using NMF-derived profiles in a large sample of French adults

Abstract: Purpose: This study, conducted in participants of the NutriNet-Santé cohort, aims to identify dietary pesticide exposure profiles (derived from Non-negative Matrix Factorization) from conventional and organic foods among a large sample of general population French adults.Methods: Organic and conventional dietary intakes were assessed using a self-administered semi-quantitative food frequency questionnaire. Exposure to 25 commonly used pesticides was evaluated using food contamination data from Chemisches und V… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 37 publications
0
7
0
Order By: Relevance
“…Various epidemiological studies reported a correlation between occupational exposure to these products and the development of pathologies, such as cancers, neurodegenerative diseases, and metabolic disorders [108][109][110][111]. Moreover, recent population studies (Nutrinetcohort in France) showed that the consumption of organic food correlated with a significant decreased risk of metabolic disease and cancer [112][113][114]. In addition, pesticides are bioactive compounds that exert an impact on various pathways underlying diseases [115].…”
mentioning
confidence: 99%
“…Various epidemiological studies reported a correlation between occupational exposure to these products and the development of pathologies, such as cancers, neurodegenerative diseases, and metabolic disorders [108][109][110][111]. Moreover, recent population studies (Nutrinetcohort in France) showed that the consumption of organic food correlated with a significant decreased risk of metabolic disease and cancer [112][113][114]. In addition, pesticides are bioactive compounds that exert an impact on various pathways underlying diseases [115].…”
mentioning
confidence: 99%
“…First, on the environmental level as organic production systems also exhibit improved energy efficiency (60), better biophysics and biological quality of soils (57,61) and are valuable for plant and animal biodiversity (57,60,61). Second, on the sanitary level, as high plant-based diets based on organic agriculture may lead to much lower exposure to pesticide residues (22,62,63), motivating the promotion of plant products produced without synthetic pesticides in the new French food-based dietary guidelines (64).…”
Section: Discussionmentioning
confidence: 99%
“…The degradation ability of PYRs by recombinant Est804 was determined. Cypermethrin (CYP), fenpropathrin (FE), and lambda-cyhalothrin (LCT), which are frequently used for agricultural products and environments ( Cámara et al, 2020 ; Rebouillat et al, 2021 ; Xiao et al, 2021 ), were used as the degradation substrates, and GC-2010PLUS gas chromatography equipment produced by Shimadzu Company in Japan was used for the quantitative analysis. The standard mixture of CYP, FE, and LCT was prepared with a BR buffer solution of pH 7.5 to obtain a final concentration of 6 mg/L.…”
Section: Methodsmentioning
confidence: 99%